2012
DOI: 10.20870/productions-animales.2012.25.2.3207
|View full text |Cite
|
Sign up to set email alerts
|

Les rationalités du travail avec les animaux d'élevage : produire, vivre ensemble et se construire

Abstract: Pour les zootechniciens, comprendre la diversité des rapports au travail des éleveurs est un préalable nécessaire à la conception de systèmes d’élevage qui soient plus durables. Pour rendre compte de cette diversité, nous mobilisons trois recherches portant sur la dimension affective, le sens moral et le rapport subjectif au travail en élevage, fondées sur des enquêtes auprès d’éleveurs. Celles-ci montrent que, du point de vue des personnes enquêtées, travailler avec des animaux d’élevage, ce n’est pas seuleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
2
0
5
Order By: Relevance
“…Dufour and Dedieu (2010) showed that the connection of farmers to their work is diverse, finding in dairy cow farming (Massif Central, France) three types: The first type wants an organized work, as a sign of modernity (taking into account the issue of work productivity and/or the need to have free time like other professions), the second type considers working with the animals as a passion and does not count their time, and for the third type, the work is overwhelming, difficult, and endured. Recently, work has been undertaken to complete the analysis of organization by the WAM by looking at the meaning of job and the productivity of the work (Fiorelli et al 2012;Chauvat et al 2016).…”
Section: What About Other Work Dimensions?mentioning
confidence: 99%
See 1 more Smart Citation
“…Dufour and Dedieu (2010) showed that the connection of farmers to their work is diverse, finding in dairy cow farming (Massif Central, France) three types: The first type wants an organized work, as a sign of modernity (taking into account the issue of work productivity and/or the need to have free time like other professions), the second type considers working with the animals as a passion and does not count their time, and for the third type, the work is overwhelming, difficult, and endured. Recently, work has been undertaken to complete the analysis of organization by the WAM by looking at the meaning of job and the productivity of the work (Fiorelli et al 2012;Chauvat et al 2016).…”
Section: What About Other Work Dimensions?mentioning
confidence: 99%
“…It sheds new lights on the farmer's perception of his work, and on his ability to analyze and change his system. Other disciplines have been used to analyze and complete WAM data, with more sociological and psychological approaches (meaning of the job, work representation, suffering at work Fiorelli et al 2012;Kling-Eveillard et al 2012;Porcher 2017), or ergonomic approaches (Sarzeaud and Chauvat 2011).…”
Section: Contribution To Advice Research and Trainingmentioning
confidence: 99%
“…Comme dans l'ensemble de la société, le besoin de reconnaissance et de réalisation individuelle dans le travail croît en agriculture (Fiorelli 2010), avec pour l'élevage cette dimension supplémentaire de l'affectif envers les animaux. Plusieurs auteurs interrogent alors certaines dynamiques de l'élevage (agrandissement, intégration, industrialisation) selon qu'elles permettent ou non l'expression de la subjectivité de chacun (Fiorelli et al 2012) et le développement ou non de sa capacité à produire ses propres normes de travail (Nicourt et Cabaret 2011).…”
Section: / Evolutions Des Identités Et Du Rapport Au Travailunclassified
“…Ce cadre permet de mettre à jour les tensions qui s'exercent entre ce qu'attendent les personnes de leur travail en élevage et ce que produit l'organisation, et de repérer ce qui est central dans l'association entre ces deux dimensions. Certaines situations de malaises d'éleveurs ou de salariés s'expliquent ainsi par le décalage entre les impératifs d'efficience et celles d'une relation paisible avec les animaux dans les grands troupeaux (Fiorelli et al 2012). (Dedieu et al 2000).…”
Section: / Les Productions De Connaissances Et De Méthodes Sur Le Traunclassified
“…D'autres dimensions du travail ont été explorées en collaboration avec des économistes pour la productivité (Charroin et al, 2012), des sociologues pour les rationalités subjectives (Fiorelli et al, 2012) et le sens du métier (Dufour et Dedieu, 2010).…”
Section: Introductionunclassified